Aqueous tape casting of titanium-doped lithium metazirconate (Ti-Li2ZrO3) sheets for solid-state electrolyte applications - Orsetti, Nicolás Gabriel (2025)
Ti-doped lithium zirconate (LZTO) sheets were successfully made by aqueous tape casting, by starting from an innovative colloidal synthesis route and optimizing the colloidal processing parameters. Zeta potential and particles size measurements, together with rheological characterization, were performed to adjust the slip composition. Then, the suspension with 1.0 wt% of ammonium polyacrylate dispersant (APA) and solid loading of 31 vol.% resulted in flat and flexible sheets, thinner than 450 µm, by adding 20 wt% of acrylic binder emulsion. After annealing at 1150 °C/15 h, LZTO sheets densified up to 85.5 %, presented a microstructure with grains of 6.4 µm in diameter, and exhibited electrical conductivity values in the order of 10−7, 10−6 and 10−5 S·cm−1 at 350, 450 and 600 °C, respectively. Besides, XRD phase analysis revealed monoclinic Li2ZrO3 and minor ZrO2 impurities originated from Li2O volatilization during sintering, but no sign of TiO2 segregation, indicating the formation of Li2Zr1-XTiXO3 solid solution.